Motivation and Work Discipline: Key Factors Influencing Employee Productivity at PT. Bangkit Maju Bersama, Tangerang - Susilawati, Nur; Salami, Muhammad Musyfiq (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aimed to explore how motivation and work discipline impact the productivity of employees at PT. Bangkit Maju Bersama, analyzing both individual and combined effects. An associative research design was employed, utilizing random sampling to select a group of 50 respondents. The data were examined through various statistical methods, including validity and reliability tests, classical assumption tests, regression analysis, correlation analysis, determination coefficient analysis, and hypothesis testing. The findings revealed that motivation significantly influences employee productivity, accounting for 51.4% of the variability in performance outcomes. Similarly, work discipline was found to have a notable impact, explaining 42.6% of the productivity variance. When considering both factors together, they accounted for 62% of the total effect on employee productivity, highlighting a substantial interactive influence. These results underscore the critical roles that both motivation and work discipline play in enhancing work productivity. The implication of this study suggests that organizations must prioritize fostering a motivating work environment alongside reinforcing disciplined work practices. This dual focus not only boosts employee morale but also enhances compliance with organizational standards, ultimately leading to greater productivity. Hence, effective management strategies should be developed to enhance motivational levels and establish clear disciplinary guidelines, as these elements are essential for achieving optimal performance within the workforce.